Inside Back Cover: Bioorthogonal Lanthanide Molecular Probes for Near‐Infrared Fluorescence and Mass Spectrometry Imaging (Angew. Chem. Int. Ed. 43/2022). Issue 43 (30th September 2022) - Jin, Guo‐Qing; Sun, De‐en; Xia, Xiaoqian; Jiang, Zhi‐Fan; Cheng, Bo; Ning, Yingying; Wang, Fuyi; Zhao, Yao; Chen, Xing; Zhang, Jun‐Long
Abstract : The concept of "killing two birds with one stone" is illustrated in the image. Clickable lanthanide molecular probes are drawn as arrowheads and the two imaging methods NIRF and SIMS are shown as two eagles, the silhouettes of which are composed of elements from the near‐infrared fluorescence and mass spectrometry images, respectively. Dual‐modal NIRF‐SIMS imaging has been achieved with these clickable lanthanide molecular probes, as reported by Yao Zhao, Xing Chen, Jun‐Long Zhang et al. in their Research Article (e202208707) .